Cluster-based aquaculture growth - Zhang, Xiaobo; Chen, Qingqing; Fang, Peixun (International Food Policy Research Institute, 2019)
As shown in Chapter 3, fish production appears to be largely clustered and the number of fish farmers, feed traders, and fish traders have all experienced rapid growth since 2008, roughly in the same magnitude. The first objective of this chapter is to quantify the trend of clustering. Based on the fish value chain survey and mesolevel primary data, we show that fish production has indeed become clustered over time. When a large number of actors work on the same sector in a limited area, the competition is inherently intense. A question arises: Why do people still want to co-locate to work on similar businesses? The cluster must create some collective efficiency, which offsets the adverse effect on profit margin due to strong competition (Schmitz 1995). Better access to market, easy learning from others, and labor pooling are the three most noted features of positive externalities in clusters (Marshall 1920). In developing countries, clustering can help to alleviate entrepreneurs’ financial constraints, a major limiting factor to private sector development, by lowering capital barriers to enter and providing trade credit for operation (Ruan and Zhang 2009; Ali, Peerlings, and Zhang 2014).